2017
DOI: 10.7150/thno.16532
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolin-targeted Extracellular Vesicles as a Versatile Platform for Biologics Delivery to Breast Cancer

Abstract: Small interfering RNAs (siRNA)/microRNAs (miRNA) have promising therapeutic potential, yet their clinical application has been hampered by the lack of appropriate delivery systems. Herein, we employed extracellular vesicles (EVs) as a targeted delivery system for small RNAs. EVs are cell-derived small vesicles that participate in cell-to-cell communication for protein and RNA delivery. We used the aptamer AS1411-modified EVs for targeted delivery of siRNA/microRNA to breast cancer tissues. Tumor targeting was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(109 citation statements)
references
References 62 publications
3
106
0
Order By: Relevance
“…Immune response to the engineered EVs was investigated. Serum associated cytokines IFN-α and TNF-α were measured in mice treated with EV-AS1411-let-7, with no statistically significant difference found when compared to a PBS treated group [36].…”
Section: Employing Evs To Increase Persistence and Targeting Of Theramentioning
confidence: 88%
See 1 more Smart Citation
“…Immune response to the engineered EVs was investigated. Serum associated cytokines IFN-α and TNF-α were measured in mice treated with EV-AS1411-let-7, with no statistically significant difference found when compared to a PBS treated group [36].…”
Section: Employing Evs To Increase Persistence and Targeting Of Theramentioning
confidence: 88%
“…AS1411 has shown inhibition of tumor activity and low systemic toxicity in a Phase II clinical trial [35]. EVs were isolated from murine dendritic cells, mixed with AS1411 overnight to coat the EVs, and then EV-AS1411 were engineered by electroporation to carry miR-let-7 [36]. Immunocompromised mice received IV EVs-AS1411-let-7 or conjugated AS1411-let-7.…”
Section: Employing Evs To Increase Persistence and Targeting Of Theramentioning
confidence: 99%
“…Wang et al reported that AS1411, DNA aptamermodified EVs-loaded with Cy5-labeled let-7, could effectively accumulate in tumor tissues and suppress tumor growth when injected intravenously [98]. In another study, researchers demonstrated that the systemic administration of brain metastatic cancer cell-derived EVs containing miRNA-181c promoted brain metastasis and destruction of the blood-brain barrier (BBB) [99].…”
Section: Cell-derived Membrane Vesiclesmentioning
confidence: 99%
“…The foreseeable identification of cancer EV‐specific DNA and “glycan signature” may further enable their capture for clinical diagnostic purposes. On the other hand, researchers have been decorating EV outer membrane for targeted delivery such as employing EV‐labeled with c(RGDyK) to cross the blood–brain barrier and target brain lesions, as well as with aptamers AS1411 to recognize nucleolin on breast cancer cells …”
Section: Ev Biology and Cancermentioning
confidence: 99%